Source-driven remobilizations of nutrients within stem wood in Eucalyptus grandis plantations - Sette Jr., Carlos Roberto; Laclau, Jean-Paul [UNESP]; Tomazello Filho, Mario; Moreira, Rildo M.; Bouillet, Jean-Pierre; Ranger, Jacques; Almeida, Julio Cesar Raposo (Springer Nature, 2013)
Nutrient remobilizations in tree ligneous components have been little studied in tropical forests. A complete randomized block design was installed in Brazilian eucalypt plantations to quantify the remobilizations of phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sodium (Na) within stem wood. Three treatments were studied: control with neither K nor Na addition (C), 3 kmol ha-1 K applied (+K), and 3 kmol ha-1 Na applied (+Na). Biomass and nutrient contents were measured in the stem wood of eight trees destructively sampled at 1, 2, 3 and 4 years after planting in each treatment and annual rings were localized on discs of wood sampled every 3 m in half of the trees. Chemical analyses and wood density measurements were performed individually for each ring per level and per tree sampled. Nutrient remobilizations in annual rings were calculated through mass balance between two successive ages. Our results show that nutrient remobilizations within stem wood were mainly source-driven. Potassium and Na additions largely increased their concentration in the outer rings as well as the amounts remobilized in the first 2 years after the wood formation. The amount of Na remobilized in annual rings was 15 % higher in +Na than in +K the fourth year after planting despite a 34 % higher production of stem wood in +K leading to a much higher nutrient sink. A partial substitution of K by Na in the remobilizations within stem wood might contribute to enhancing Eucalyptus grandis growth in K-depleted soils. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Eucalypt; Potassium; Resorption; Retranslocation; Sodium; Trunk; Eucalypt plantations; Eucalyptus grandis; Nutrient contents; Partial substitution; Calcium; Chemical analysis; Forestry; Wood; Nutrients; Chemical Analysis; Eucalyptus